PKM Pendampingan Guru SD YPPK Hati Kudus Merauke dalam Membuat Bahan Ajar Inovatif Berbasis Etnomatematika Papua - Fredy, Fredy; Purwanty, Ratna; Rapsanjani, Hafsemi; Yohanes, Rizki Adri; Ismail, My; Day, Wa Ode Siti Hamsinah (LPPM Universitas Flores, 2023)
The unavailability of innovative teaching materials that contain a numeracy literacy component is the main obstacle for SD YPPK Hati Kudus teachers in the success of the GLS program. The teaching materials that have been used so far are teaching materials that already exist, are provided by the government and are left to be used, there has been no effort to prepare and compile them yourself, even though the teacher realizes that they are not in accordance with the characteristics, social and culture of students. YPPK Hati Kudus Elementary teachers also realize that innovative teaching materials are needed and require creativity in making them appropriate to Papuan social and culture so that students become interested, active and not bored in learning. The solution offered is assistance in making innovative teaching materials based on Papuan ethnomathematics as an effort to increase students' active learning and numeracy literacy competencies. PKM consists of preparation, introduction, technical assistance, implementation. The results of the dedication show an increase in teacher understanding and skills in making innovative teaching materials based on Papuan ethnomathematics